Empirical Estimates of Data on the Dynamics of Changes in the World Foreign Exchange Market - Lyashenko, V.; Bril, M.; Pyvavar, I. (IJAMSR, 2021)
Empirical assessments are generalized characteristics of the data, processes and phenomena that are being investigated. Such estimates are based on real data, which are considered from some historical perspective. Particular attention is paid to such assessments in the study of processes, events, phenomena that occur in different spheres of the economy. This allows you to assess the situation from different points of view, justify and make the necessary decisions. Among the different spheres of the economy and areas of economic activity, the need for foreign exchange transactions should be highlighted. In a market economy, during the period of globalization, such a need arises for many business entities (access to raw materials markets, sales markets, implementation of cooperation, and provision of conditions for the division of labor). This is due to the fact that the conduct of economic activities requires the establishment of a correspondence between the monetary units of different countries. In this regard, the paper considers an approach to assessing data on the dynamics of changes in the world foreign exchange market. This approach is based on methods of wavelet analysis, where an approach to data estimation based on wavelet coherence is chosen. At the same time, the ideology of the formation of cross-rates of currencies is also taken into account. We considered different currency pairs and constructed estimates of their wavelet coherence. Conclusions are drawn about the dynamics of each of the currency pair s that we are considering. The results of the analysis of estimates of wavelet coherence for the currency pairs that we are studying are generalized. Research results are based on real data. All results are presented in the form of visual graphs, which allows the continuation of similar studies. It is shown that the results of the study are in agreement with the results of other authors.
Keywords: wavelet analysis; currency pair